Body balance of male football players aged 7-10: pilot study - Lichota, M.; Górniak, K.; Sacewicz, T.; Sadowska, D. (Theory and Practice of Physical Culture, 2021)
Objective of the study - body balance is an element needed to perform activities of daily living and do sports. The aim of this study was to evaluate and compare body balance of male football players aged 7-10.